2011
DOI: 10.1186/cc10257
|View full text |Cite
|
Sign up to set email alerts
|

Recommended β-lactam regimens are inadequate in septic patients treated with continuous renal replacement therapy

Abstract: IntroductionSepsis is responsible for important alterations in the pharmacokinetics of antibiotics. Continuous renal replacement therapy (CRRT), which is commonly used in septic patients, may further contribute to pharmacokinetic changes. Current recommendations for antibiotic doses during CRRT combine data obtained from heterogeneous patient populations in which different CRRT devices and techniques have been used. We studied whether these recommendations met optimal pharmacokinetic criteria for broad-spectru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
193
6
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(223 citation statements)
references
References 51 publications
21
193
6
3
Order By: Relevance
“…Our PD data resembled the data of others, suggesting that the probability of target attainment (probability of reaching fT.MIC564 mg/ml>50%) was not 100% (10,19,20).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Our PD data resembled the data of others, suggesting that the probability of target attainment (probability of reaching fT.MIC564 mg/ml>50%) was not 100% (10,19,20).…”
Section: Discussionsupporting
confidence: 72%
“…PK parameters for piperacillin in our study resembled those parameters reported in the work by Seyler et al (10), and they are notably differ from those parameters published in a commonly used prescribing guide ("The Green Book") (16). Protein binding was lower, volume of distribution was higher, and half-life was longer than described in this prescribing guide (16).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Consequently, many of the antibiotic doses that seemed to be appropriate for patients receiving RRTs in the ICU in the past are probably insufficient today (32,33). Pharmacokinetic and pharmacodynamic studies like the one by Lorenzen et al (7) need to continue to be conducted for all types RRT, to begin to reduce the infectious mortality rate in this vulnerable patient population.…”
mentioning
confidence: 99%